Species composition of glass eels (Anguilla spp.) recruiting to the Palu River, Central Sulawesi [Komposisi spesies glass eels (Anguilla spp.) yang beruaya di muara Sungai Palu, Sulawesi Tengah] - Novalina Serdiati; Samliok Ndobe; Abigail Moore; Deddy Wahyudi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2013)
Demand for tropical eel seed has been increased and many tropical eel populations are under pressure. To conserve eel biodiversity and manage eel populations sustainably, it is necessary to identify eel species and their recruitment patterns at regional and watershed scales. The research objective was to determine the species composition and temporal recruitment patterns of glass eels recruiting to Palu River in Central Sulawesi. Glass eels sampling were conducted in January-April 2009, May-November 2010 and April-December 2011. Identification under anaesthetic (15-17.5 ppm clove oil solution) was based mainly on the number of ano-dorsal vertebrae (ADV). Species composition was dominated by two commercially species, Anguilla marmorata and A. bicolor pacifica with substantial variation and no clear temporal patterns. Specimens of other species that important from conservation and biodiversity aspects were present at each month but cannot be accurately identified using the ADV method. DNA analysis method is required to identify these specimens. Abstrak Permintaan benih ikan sidat tropis meningkat dan banyak populasi sidat tropis telah mengalami tekanan. Untuk meles-tarikan keanekaragaman hayati ikan sidat dan mengelola populasi sidat secara berkelanjutan, perlu identifikasi spesies maupun pola rekrutmennya pada skala regional maupun daerah aliran sungai. Tujuan penelitian adalah menentukan komposisi jenis dan pola rekrutmen glass eels secara temporal di Sungai Palu, Sulawesi Tengah. Sampling dilakukan pada bulan Januari-April 2009, Mei-November 2010, dan April-Desember 2011. Identifikasi contoh ikan dalam kea-daan pingsan (menggunakan larutan minyak cengkeh 15-17.5 ppm) terutama didasarkan pada jumlah anodorsal vertebrae (ADV). Komposisi jenis didominasi oleh dua spesies bernilai ekonomis, yaitu Anguilla marmorata dan Anguilla bicolor pacifica, namun sangat bervariasi tanpa pola musiman atau tahunan yang jelas. Setiap bulan terdapat beberapa spesimen dari spesies lain, yang penting dari aspek konservasi dan biodiversitas, namun tidak dapat diidentifikasi secara pasti dengan metode ADV. Untuk mengidentifikasi spesimen tersebut dibutuhkan metode analisa genetik (DNA).